Hospital based prospective longitudinal clinical and immunologic study of 179 patients of primary anti‐phospholipid syndrome. (26th October 2013) - Singh, Nand K.; Behera, Dibya R.; Agrawal, Ankit; Singh, Mahendra Narayan; Kumar, Vikash; Godhra, Manoj; Gupta, Anurag; Yadav, Devesh P.; Singh, Usha; Pandey, Lakshmi Kant; Matah, Manjari
Abstract: Aim: To study the clinical and immunological features of primary antiphospholipid syndrome (APS), and to analyze the differences between primary APS and APS associated with autoimmune rheumatic disease (ARD/APS). Methods: This prospective, longitudinal study, carried out from December 2004 to July 2011 included 179 patients with primary APS and 52 patients of ARD/APS diagnosed as per modified 2006 Sapporo's Criteria. Results: Out of 179 patients of primary APS, 12 were male and 167 were female. The mean age at the time of study entry was 27 ± 4.33 years. Venous thrombosis was noted in 33 (18.43%) patients. Seventeen patients had deep vein thrombosis and 11 (7.19%) had cortical vein and/or cortical sinus thrombosis. Arterial thrombosis was noted in 19 (10.61%) patients, out of which nine had intracranial arterial thrombosis. Thirty‐two (17.85%) had recurrent early fetal losses (< 10 weeks) and 97 (54.18%) had late fetal loss (> 10 weeks). Immunoglobulin G (IgG) and IgM aCLA were present in 141 (78.77%) and 32 (17.87%) patients respectively, whereas lupus anticoagulant was present in 99 (55.3%) patients. In patients with bad obstetric outcome, lupus anticoagulant positivity was significantly more prevalent ( P  < 0.05) than aCLA positivity. Both venous and arterial thrombosis were significantly more common ( P  < 0.05) in ARD/APS. However, late fetal loss was significantly more prevalent ( P  < 0.001) in primary APS. Conclusion: Primary APS may lead to a variety of clinical manifestations due to venous and/or arterial thrombosis, which at times may be lethal. It is also an important cause of early and late pregnancy loss(es) and other pregnancy morbidities.